Evaluation of the physicochemical and textural properties of pomelo fruit following storage - Panmanas Sirisomboon; Ravipat Lapchareonsuk (My University, 2012)
Evaluation of the physicochemical and textural properties of pomelo fruit following storage. Abstract - Introduction. Because of the long transportation times and storage durations that are often experienced, it is important to understand how pomelo properties change over time; that will be indicative of how long samples can be stored before they drop below acceptable quality limits. As no information is available regarding storage of pomelo fruit in the literature, the goal of our work was to study the change in pomelo physicochemical and textural properties following storage over a period of approximately 4 months. Materials and methods. The changes in physical, chemical and textural properties of commercial pomelo fruit were extensively evaluated over the course of a 4-month storage period. The correlation among physical, color, chemical and textural properties were also assessed. Results. Color properties (L*, a*, b*) changed significantly with storage; however, they did not change much during the initial 45 days of storage. The change in soluble solids content (SSC), acidity (A) and the ((SSC) / (A)) ratio suggested that pomelo fruit should not be stored for more than 75 days. Crucially, our study demonstrates that the a* parameter (greenness, R = -0.556) cor- relates best with the chemical property the ((SSC) / (A)) ratio, which is a recognized measurement of the consumer acceptability of citrus fruit. This means that measuring a* is a non-destructive way of monitoring the taste characteristics of pomelos in storage. This property also correlated well with the average firmness of the fruit and with the flesh texture. Conclusion. This fundamental informa- tion on the pomelo fruit could prove useful in the physical handling and processing of the fruit by breeders and postharvest technologists as well as distributors, market agents, importers and exporters. Thailand / Citrus grandis / fruits / pomelos / storage / physicochemical properties / texture / rheological properties
Keywords: Texture (cosmology); Postharvest Quality and Shelf Life Management